Research and application progress of deep ocean water industry in the United States. Issue 1 (January 2021) - Zhang, Yanan; Hao, Xiaocui; Wu, Dan; Guo, Shuyuan; Gao, Chunjuan
Abstract: Firstly, Hawaii as the main source of water exploitation for deep ocean water (DOW) in the United States was described. And the main methods of collecting DOW were also introduced. Then, the development of DOW in the US from the stage of direct utilization to that of multistep utilization was discussed. Finally, the industry, products and market scale of DOW in the US were explained. The DOW industry in the United States had achieved very good economic benefits. In the future, with people's deep understanding of the deep sea and the continuous progress of technology, the development of DOW would be more diversified.